PENGARUH MOBILISASI DINI TERHADAP PENYEMBUHAN LUKA POST OPERASI SECTIO CAESAREA DI RUANG NIFAS RS BHAYANGKARA MANADO - Yannerith Chintya; Ariska Ariska; Erika S.P. Marenda (Yayasan Syalom Cipta Sumikolah, 2024)
Early mobilization management is one of the factors that influences post-operative wound healing and can reduce the risk of complications. Early mobilization is a policy to guide sufferers as quickly as possible to get out of bed and walk. Early mobilization can speed up the wound healing process because early mobilization can train the muscles for the wound healing process. The aim of the research is to determine the effect of early mobilization on post-caesarean section wound healing in the Postpartum Room at Bhayangkara Hospital, Manado.This research is quantitative using the type of research design used is